The The Effect of Think Talk Write (TTW) Strategy Toward Students Announcement Writing Skill at The Eleventh Grade of SMAN 9 Pandeglang in Academic Years 2025/2026 - Mia Kurniawati; Riandi Riandi; Nur Azmi Rohimajaya (Sumule Indonesia Publishing, 2026)
The Effect of Think Talk Write (TTW) Strategy Toward Students Announcement Writing Skill at the Eleventh Grade of SMAN 9 Pandeglang in Academic Years 2025/2026. The study was initiated by observing a persistent gap in the writing of announcements by eleventh-grade students at SMAN 9 Pandeglang. This deficiency suggests a critical need for pedagogical interventions to address challenges in constructing clear, informative, and structurally sound announcement texts, thereby enhancing overall communicative competence. The primary objective of this quantitative study was to empirically evaluate the impact of implementing the Think-Talk-Write (TTW) strategy on improving students' announcement-writing skills. Using a robust quasi-experimental design, the study recruited a carefully selected sample of 64 eleventh-grade students. This sample was strategically divided into an experimental group (32 students) and a control group (32 students) to facilitate direct comparison. Writing proficiency was systematically assessed through pre-test and post-test evaluations using a standardized writing test instrument. Data analysis, conducted using an independent t-test in SPSS version 22, revealed a statistically significant difference in performance. Specifically, the experimental group, which received the TTW strategy intervention, achieved a substantially higher mean post-test score (80.94) compared to the control group (65.75), with a significance value of 0.000 (p < 0.05). Based on these compelling findings, it is conclusively determined that the Think-Talk-Write (TTW) strategy is a highly effective pedagogical tool for significantly enhancing students’ writing skills in announcements.